Numerical simulation for determining the measurement uncertainty for the calibration of mass standards by transfer artefacts. (December 2022) - Lehrmann, Katharina; Härtig, Frank; Tutsch, Rainer
Abstract: Monte Carlo methods are appropriate for determining the manufacturing accuracy and measurement uncertainty for the calibration of mass standards using sorption, duplex and buoyancy artefacts that are referred to as transfer artefacts. Systematic influences and their application-specific measurement uncertainty can be calculated for the important parameters mass, surface area and volume. Since accurate volume measurements are complex, the evaluation of the uncertainty contribution is important. The input variables of the simulations result from the specified manufacturing tolerances as well as from the measurement uncertainties of the coordinate measuring machines employed. The developed model allows the transfer artefacts described to be calculated with a uniform approach according to the specifications of the GUM. Results for silicon transfer artefacts with a nominal mass of 1 kg are presented and discussed.